Level of academic stress among e-learning student-athletes / Vincent A. Parnabas, Julinamary Parnabas, Antoinette Mary Parnabas - Parnabas, Vincent A.; Parnabas, Julinamary; Parnabas, Antoinette Mary (Penerbit UiTM (UiTM Press), 2015)
Academic stress refers to the impact that educational organizations may produce on their students by imposing too many tasks with great competition from other students. Lower academic stress has been linked to higher performance in studies through e-learning. The aim of this research was to identify and compare the level of academic stress among different types of e-learning users among student-athletes’ such as Frequent, Partial and Rare-user. The 34 items of Academic Stress assessing seven factors were used to collect data. One hundred and twenty students were selected to participate in this study. The results showed that the Group Stress (x̅=18.1146) and Peer Stress (x̅=14.4036) were higher in studying among the Frequent e-learning users. It was identified that Time Management Stress (x̅=14.1621) was higher among the Partial e-learning users. The Rare e-learner users’ stress level was higher in Teachers Stress (x̅=17.3397), Result Stress (x̅=19.1528), Test Stress (x̅=18.3346) and Self-inflicted Stress (x̅=15.1019). The findings in this study provide a useful insight to educators to motivate the rare-users to engage in e-learning in order to reduce their academic stress, since high level of academic stress is associated with poor academic achievement.